(untitled) (Asian Journal of Agriculture, 2025)
Abstract. Afifah N, Susilowati A, Purwanto E. 2025. Morphological and genetic variation of cassava (Manihot esculenta) based on DNA markers barcoding rbcL and ITS. Asian J Agric 9: 255-263. The cassava crop holds significant economic value as both a food source and a commercial crop. This study aims to characterize cassava varieties using morphological and molecular methods. Five cassava varieties were identified in Boyolali District, Central Java, Indonesia: M, U, KP, HM, and MH. Morphological observations following the guidelines in the book Selected Morphological and Agronomic Descriptors for the Characterization of Cassava. Molecular observations were conducted using a DNA barcoding technique, with the rbcL and ITS as DNA markers. The research involved several stages, beginning with the isolation of genomic DNA using the Genaid plant DNA extraction kit, then the visualization of the genomic DNA by using gel electrophoresis and amplification of gene targets—subsequently, bidirectional Sanger sequencing. The DNA sequences of each sample were subjected to BLAST analysis on the NCBI website for species identification. The NTSYSpc was utilized to examine relationships based on morphological characteristics. For molecular characteristics, MEGA11 was used for nucleotide composition analysis, genetic distance calculation, and phylogenetic tree construction. The morphological analysis revealed substantial variations in the colors of leaf petioles, the distance between stem nodes, and the texture of tuber bark. All five cassava varieties exhibited a high degree of genetic similarity to Manihot esculenta Crantz, demonstrated by their high query coverage and E-values.